Green Accounting Implementation and Its Influence on Corporate Environmental Responsibility Disclosure in Indonesian Public Companies - Syarkani, Yofy (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This study investigates the implementation of green accounting and its influence on corporate environmental responsibility disclosure among public companies in Indonesia through a comprehensive literature review. As environmental concerns continue to shape corporate governance globally, the adoption of green accounting practices has become increasingly relevant in emerging economies. This paper synthesizes previous research findings to evaluate how green accounting frameworks contribute to the transparency and accountability of environmental reporting. By analyzing scholarly articles, regulatory documents, and industry case studies published between 2010 and 2024, the study identifies key drivers, barriers, and patterns in environmental disclosure. It further explores how Indonesian public companies respond to environmental pressures and regulatory demands through green accounting mechanisms. The findings suggest that while regulatory frameworks support disclosure initiatives, practical implementation remains inconsistent due to limited awareness and resource constraints. Moreover, companies with proactive environmental strategies tend to disclose more comprehensive sustainability reports. This paper contributes to existing knowledge by contextualizing global green accounting practices within the Indonesian corporate landscape. The study also highlights the need for enhanced policy enforcement and capacity building to strengthen disclosure quality. Ultimately, the review underscores the strategic role of green accounting in promoting long-term environmental accountability in corporate reporting.